PROTECTION OF THE RIGHT TO LIFE FOR THE INDIGENOUS PEOPLE OF PORT NUMBAY IN THE YOUTEFA BAY AREA OF JAYAPURA CITY - Elisa Reba, Yusak (Penerbit Lafadz Jaya, 2024)
This study aims to analyze the Protection of the Right to Life for the Indigenous People of Port Numbay in the Youtefa Bay Area in Jayapura City. This type of research is juridical normative using statutory and conceptual approach methods. This research was conducted in Jayapura City in the area of Abepura District and South Jayapura District. The technical analysis of the legal material used is qualitative described. The results showed that (i), the Jayapura City government has tried to protect the right to life for the Port Numbay indigenous people who inhabit Youtefa Bay friends by establishing and enforcing Jayapura City Regional Regulation Number 7 of 2012 concerning Waste Management and Jayapura City Regional Regulation Number 15 of 2011 concerning the Implementation of Hygiene. Even so, the two Regional Regulations still display normative weaknesses, there are shortcomings in regulation and weak imposition of criminal sanctions and administrative sanctions for violators; and (ii), the Jayapura City Regional Regulation on Waste Management and the Jayapura City Regional Regulation on Hygiene Implementation, have not had significant implications for the protection of the right to life of the Port Numbay indigenous people who inhabit the Youtefa Bay area.